Achieving superior high-strength geopolymer via the synergistic effect of traditional oven curing and microwave curing. (28th November 2022) - Dong, Zian; Ma, Hongwen; Feng, Wuwei; Nie, Yimiao; Shi, Hao
Highlights: Effect of particle size ratio on the compressive and flexural strength of geopolymers is investigated. Effects of different pre-curing temperatures and curing times on the flexural strength of the geopolymer are compared. How to obtain high strength geopolymer by microwave curing is studied. Microstructure and reaction mechanism of microwave cured geopolymer and conventional cured geopolymer are studied. Abstract: Geopolymerization technology provides a green, pollution-free and economical method to solve the problem of massive accumulation of mine tailings in today's society. The fabrication of geopolymer generally need a combination of oven curing and room temperature curing to take more than 3 days to have durable strength, which leads to the low production efficiency of the massive industrial production. In this paper, the feasibility of preparing spodumene tailings based high-strength geopolymer by the combination of oven curing and microwave curing was investigated. The obtained geopolymer products demonstrated excellent mechanical properties within 7 h, which indicates significantly improved production efficiency. Via the optimization of aggregate gradation and solid/liquid ratio, we achieved geopolymer with record-breaking compressive strength of 203.5 MPa and flexural strength of 34.1 MPa (exceeds 90 % of 28 days strength) after a combination of oven curing for 14 h and microwave curing for 16 min. The compressive and flexural strength increases by 30.5 % and 47.6 %, respectively, compared with those under conventional curing solely, and also increases by 128.1 % and 101.6 %, respectively, if compared to the sample cured by microwave only. The achieved high strength is mainly ascribed to synergistic effect of oven curing and microwave curing on the geopolymer matrix with optimized ratio of Si/Al and Na/Al which causes polymerization reaction almost completed in the early stage and leads to dense microstructure of the products. The obtained ultrahigh-strength geopolymer also has good thermal shock and freeze–thaw stability, and shows great application prospect in the field of construction and building materials.